1994
DOI: 10.1007/bf01676891
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the splenic flexure of the colon: Report of a case

Abstract: A 51-year-old Japanese man underwent resection of a tumor in the splenic flexure of the colon, which proved to be squamous cell carcinoma. At the time of presentation, the liver was found to have multiple metastases. On the 39th postoperative day, the patient died of liver failure. An autopsy demonstrated metastatic nodules on the pleura and parenchyma of both lungs, as well as in the liver, but failed to show any other primary squamous cell carcinoma. We emphasize that a meticulous search to disprove adenosqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Since it was first described in 1963, 15 cases of colon cancer associated with hypercalcemia have been documented, almost all of which are of adenosquamous type [7]. In only one previously reported case was hypercalcemia attributable to a pure SCC of the colon [2]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it was first described in 1963, 15 cases of colon cancer associated with hypercalcemia have been documented, almost all of which are of adenosquamous type [7]. In only one previously reported case was hypercalcemia attributable to a pure SCC of the colon [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a worse prognosis compared to adenocarcinoma and adenosquamous types; however, true survival rates remain unknown [1,2,3,4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first ever described case of SCC bowel was in 1919 by Schmidtmann . The mean age of affected individuals is between 55 and 60 with a higher preponderance in women with a ratio of 7:1 .…”
Section: Discussionmentioning
confidence: 99%
“…Only one of these has been described in the splenic flexure . Most SCCs of the bowel are advanced cancers and are usually node positive . As such, most of the cases studied presented as emergencies, that is, acute bowel obstruction or perforation.…”
Section: Discussionmentioning
confidence: 99%